A importância do estágio supervisionado e as experiências vivenciadas pelos acadêmicos do curso de Educação do Campo no município de Medicilândia - VIANA, Maria das Dores (2021)
The purpose of this essay / article is to present and analyze the experiences lived by the students of the Degree Course in Education in the Field, at the Federal University of Pará, Medicilândia Center, state of Pará, during the supervised internship in the disciplines of chemistry, physics and biology, considering the difficulties faced and the contributions that the internships provided for the teacher training of these students, considering that they were developed in rural schools, preferably in their communities of origin. The students' experiences during the internships were the object of analysis when choosing the theme. The research is based on a qualitative investigation, in which it was necessary to systematize the information gathered and organized by the students with a view to producing their reports, and which concern the perceptions of leading teachers and board members of the interned schools. The internship is relevant in teacher training, since it provides teachers in training to experience real situations in the field of work, based on this, they constitute learning that will help them in their professional teaching performance, and also allows to relate the practice with the knowledge acquired in the academy, as well as the development of skills and competences for the construction of their teaching identity and to deal with different situations that encompass the school space. And, for some academics, this is their first contact with the classroom, and in this way, the internship qualifies the student to work in rural schools, awakening in them the thought about possible actions that contribute to the improvement of teaching and learning, despite the difficulties faced within such activities and relationships.